Doppler ultrasound triggering for cardiac MRI at 7T. Issue 1 (1st December 2017) - Kording, F.; Ruprecht, C.; Schoennagel, B.; Fehrs, K.; Yamamura, J.; Adam, G.; Goebel, J.; Nassenstein, K.; Maderwald, S.; Quick, H.H.; Kraff, O.
Abstract : Purpose: A prerequisite for cardiac MR (CMR) imaging is adequate synchronization of image acquisition with the cardiac cycle. Electrocardiogram triggering may be hampered by electromagnetic interferences at high field strength. The purpose of this work is to evaluate the feasibility of Doppler ultrasound triggering for CMR image synchronization at 7T ultra‐high‐field MRI. Methods: A custom‐built Doppler ultrasound (DUS) trigger device was developed. Magnetic resonance compatibility was evaluated using E‐ and H‐field probes and flip angle maps prior to the study. Cardiac MR was performed at 7T in 13 healthy subjects using DUS and pulse oximetry for triggering. For validation of the trigger signal, the electrocardiogram, pulse, and DUS signals were compared outside of the MR room. Breath‐hold cine fast low‐angle‐shot sequences were acquired in short‐axis and four‐chamber view. Image quality was assessed by two senior radiologists and by measurement of endocardial blurring. Results: The maximal change in E‐ and H‐field distributions with and without transducer was 5%. No interferences were observed between DUS and MRI in the B1 maps and during CMR imaging. Validation of the DUS trigger signal resulted in a high correlation to the electrocardiographic signal of r = 0.99. Analysis of image and trigger quality revealed no significant differences. Conclusion: Doppler ultrasound was applied as a new trigger method in CMR at 7T. The transmission line and transducer were locally approved as 7T MR conditional, and were successfully tested for image synchronization at 7T. In the future, this method needs to be evaluated in a larger patient population. Magn Reson Med 80:239–247, 2018. © 2017 International Society for Magnetic Resonance in Medicine.